(untitled) (Texas Journal of Philology, Culture and History, 2023)
The study defined the (interim) period as a timetable for the work of the Islamic Al Da’wa Party and determined the location of the political phase in it. Then, her study focused on extrapolations and planning of the party during its period of change ( 1979-1958AD) due to the difficulties and challenges it would face when it moved to the political stage. The study came under the title (The Political Stage in the Thought of the Islamic Al Da’wa Party), and it touched on the time of the transition to the political stage, what that time required of the party capabilities, the nature of the Al Da’wa h relationship with the nation and its role in this transition, and the impact of the political circumstance subject to the control of foreign influence and the moods of the puppet rulers in it. The study also dealt with the place of transition to the political stage, and after the party divided the Muslim countries and studied the commonalities between them, Iraq, from which the beginnings of its process began, was identified as a place for the transition process. The study also examined how to move to the political stage, and what the party proposed of some methods that could be appropriate to start the process of transition to the second stage at that time. In his study, the researcher relied on a group of secret bulletins that included opinions, articles, statements, and comments of the party’s advocates, most of which were published during its first phase (change)